Why we make art and why it is taught - Hickman, Richard (Richard Douglas), 1951- (Intellect Books, 2005)
Does art have any use or real purpose in today's society? Why do governments around the world spend millions on art education? Rejecting the vogue for social and cultural accounts of the nature of art-making, this book is largely psychological in its approach to discussing art-making and its place in education. The 'we' in the title is intentionally polemical, with the author claiming a universal, ie pan-cultural basis for 'art' making activities -- or rather activities which can be described as 'creating aesthetic significance'. Developmental issues in art education are examined, together wit.